Analysis of microstructure and mechanical strength of lap joints of TZM alloy welded by a fiber laser. (March 2019) - Ning, J.; Hong, K.M.; Inamke, G.V.; Shin, Y.C.; Zhang, L.J.
Graphical abstract: Abstract: The application of molybdenum alloys to structural components is severely limited due to their poor weldability with serious defects of porosity and joint embrittlement after welding despite their high melting temperature, hot strength and creep resistance. A systematical experimental study has been conducted to explore the potential of laser welding of 0.5 mm-thick Titanium-zirconium-molybdenum (TZM) alloy in a lap welding configuration. Porosity was found to be the most serious problem in the TZM laser lap welding process. Introducing an interface gap of 0.09 mm had the most positive effect in reducing the porosity compared to using helium gas, different shielding gas flow rates, adding alloy element and different heat input rate. With the use of 0.09 mm-interface gap, the porosity of the weld joint was reduced to 3%. The tensile stress of the bead on plate (BOP) welded joint could achieve about 60% that of the base metal. The fracture stress of the lap welded joint obtained by using 0.09 mm-interface gap in tensile-shear test was about 142 MPa. The porosity and embrittlement were responsible for the reduction of the strength and ductility of the welded joint.